Protection mechanism of N,N-dimethylformamide on stability of few-layer black phosphorus - Lei, Lei; Zhang, Siyu; Lou, Wenhao; Zhang, Xuejiao; Qin, Bin; Zhao, Qing; Xing, Baoshan (Frontiers in Environmental Science, 2023)
Few-layer black phosphorus (LBP) has been widely investigated for its unique optical and electronic properties. As degradation of LBP in ambient conditions largely limited its practical applications, numerous stabilization methods were developed. Understanding stabilization mechanism is essential to development of new protection technologies for LBP. Herein, protection mechanism of the most wildly used exfoliation solvent N,N-dimethylformamide (DMF) on LBP was investigated. DMF was found to accelerate color fading of LBP in aerobic water solution. Nevertheless, dissolvable phosphorus generated from degradation of LBP in the presence of DMF accounted for only 52 ~ 57% of that generated in the absence of DMF. By measuring kinetics constants and activation energies of the degradation reactions, the protection mechanism of DMF was attributed to impede hydrolysis of phosphorus oxides. This was caused by occupation of oxidation sites on LBP through electrostatic interaction. Insoluble phosphorus oxides in addition to dissolvable phosphorus were observed in LBP and DMF system, providing further evidence for hydrolysis impeding mechanism. This finding threw mechanism light on protection effects of DMF on LBP, providing new knowledge for development of effective stabilization technologies of LBP.